Injury of the axillary artery - Krnić, Anton (Radiology and oncology (Ljubljana), 2005)
Background. Injury of the axillary artery is a life-threatening condition. Theinjury requires immediate, onplace treatment (compression) and a number of patients require prompt explorative surgery. Whenever a vascular injury is suspected, radiological follow-up (angiography), intra-operative or post-operative, should be performed. Case report. We report a case of axillaryartery injury in 28-year- old woman. Though postoperative duplex ultrasound gave an accurate finding, i.e. pre-stenotic, high resistant Dopplerwave spectrum proximal to and post-stenotic, monophasic distal to the injury, angiography was performed. It showed extensive collateral network in the axilla and the blocked perfusion in the axillary artery. The patient underwent re-operation. Thrombectomy in the axillary artery was performed, with a subsequent radical improvement of the arm perfusion. Conclusions. In these particular circumstances, duplex ultrasound displayed a characteristic pattern and the angiography might even be avoided.
Keywords: Adult; aksilarna arterija; arterije; Axillary Artery; diagnostika; Injuries; Odrasli; Pazdušna arterija; poškodbe; Surgery; Ultrasonography; ultrazvočna diagnostika